2. Presentation - Cortés Ramos, Alberto (2011)
The second presentation of theAnuario Centro de Investigación y Estudios Políticos journal (vol. 1) was given by Dr. Alberto Cortés, from a historical perspective on the creation of the Political Science program at the University of Costa Rica and the CIEP - UCR.